ALAT UKUR KAPASITOR DAN RESISTOR BERBASIS ARDUINO UNO - Ratika Ayu; Yulhan Putra Sasuna; Surojo; Zanu Saputra (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
facilitate practical activities at the Politeknik Manufaktur Negeri Bangka Belitung, especially in the Department of Electrical and Informatics Engineering, when looking at how precise it is compared to standard measuring instruments. To measure resistance, this tool uses a voltage divider circuit based on the amount of voltage that exceeds the resistor. In terms of capacitance, it is based on battery charging time. Arduino Uno is used to measure the voltage through the ADC channel and the charging time into resistance and capacitance values. the test results, it is found that the average percentage error in the resistor measurement is 2,4% with a maximum error of 10,8%, while the average percentage error is 4,7% and the maximum error is 10,5%. In general, it can be said that this tool is quite feasible to use.concluded that the designed product is quite good for practical activities.